Tuberculous Thoracic Aortic Pseudoaneurysm Associated With Spinal Tuberculosis: A Case Report and Literature Review - Chen, Yurou; Sheng, Bo; Li, Jia; Lv, Furong (Frontiers in Medicine, 2022)
Background: Thoracic aortic pseudoaneurysm associated with spinal tuberculosis is a rare but fatal condition. The risk of pseudoaneurysm rupture is extremely high and this disease needs greater awareness. The present study reported a case of thoracic aortic pseudoaneurysm caused by paravertebral cold abscess with spinal tuberculosis. Case presentation: A 35‐year‐old woman with back pain was diagnosed with thoracic aortic pseudoaneurysm with spinal tuberculosis, and endovascular aneurysm repair (EVAR) was performed. The patient’s symptoms disappeared after EVAR, following which she was discharged. Conclusions: The case highlighted that in cases where non‐enhanced computed tomography (CT) revealed that the aortic vessel was surrounded by a paravertebral abscess, magnetic resonance imaging (MRI) should be performed to confirm whether the presence of a pseudoaneurysm. Upon diagnosis of pseudoaneurysm, surgery should be performed immediately. In recent times, EVAR has emerged as a promising alternative to open surgery.